2012
DOI: 10.1111/jcpt.12005
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of prurigo nodularis with pregabalin

Abstract: In our study, pregabalin was effective for the treatment of PN. However, given the open and non-controlled study design used, a properly powered randomized controlled validation study is called for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 17 publications
2
35
0
5
Order By: Relevance
“…1 The results of this survey also support the established finding that PN confers a heavy burden on patients and that these patients likely require more frequent use of healthcare resources. In line with what is reported in the literature, 8,25,26 respondents rated immunosuppressants and gabapentinoids as the most effective systemic treatments for pruritus in PN. Sleep disturbance has been demonstrated to have serious consequences, including poor health, missed workdays and doctor visits owing to other skin conditions.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…1 The results of this survey also support the established finding that PN confers a heavy burden on patients and that these patients likely require more frequent use of healthcare resources. In line with what is reported in the literature, 8,25,26 respondents rated immunosuppressants and gabapentinoids as the most effective systemic treatments for pruritus in PN. Sleep disturbance has been demonstrated to have serious consequences, including poor health, missed workdays and doctor visits owing to other skin conditions.…”
Section: Discussionsupporting
confidence: 84%
“…Sleep disturbance has been demonstrated to have serious consequences, including poor health, missed workdays and doctor visits owing to other skin conditions. 2,[25][26][27][28][29] Of particular note is the use of antidepressants. 4,8,9 Treatment for PN is commonly standardized, and the goal of therapy is often to manage pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to nephrogenic pruritus, there is now sound evidence of the effi cacy of gabapentin and pregabalin. Moreover, case reports and one open non-controlled trial have shown that pregabalin -at a dose of 75-300 mg/day -may be effectively used in the treatment of PN-associated CP [ 28,29 ] .…”
Section: 6 Anticonvulsant Drugs: Gabapentin Pregabalinmentioning
confidence: 99%
“…In Fallberichten und einer offenen, nichtkontrollierten Studie konnte ferner dokumentiert werden, dass Pregabalin in einer Dosierung von 75-300 mg/d effektiv zur Therapie des CP bei PN eingesetzt werden kann[ 28,29 ] .Der Wirkmechanismus von Gabapentin und Pregabalin bei CP wird noch diskutiert und beruht möglicherweise auf einer Nervenmembranstabilisation durch die Blockade von Kalziumkanälen, Inhibition der Synthese des Neurotransmitters Glutamat oder durch Verstärkung GABAerger inhibitorischer Mechanismen[ 26 ] . Häufi g treten Übelkeit, Erbrechen, Schwindel oder Müdigkeit auf, die nach einigen Tagen abklingen (siehe hierzu Fachinformation).…”
unclassified
“…The developmental pathways of pain and pruritus are similar (2). Furthermore, the efficacy of pregabalin for treating pruritus has been previously reported (2)(3)(4)(5). We herein present a case in which we prescribed pregabalin for the treatment of chronic intractable itching that led to repeated cutaneous infections.…”
Section: Introductionmentioning
confidence: 76%